Mekanisme Distribusi Kekayaan dalam Ekonomi Syariah dan Relevansinya terhadap Tantangan Ekonomi Modern - Hijjatum Balighotul Qolbah; Rahmawati Rahmawati (Rashid : Journal of Economic, 2025)
Socioeconomic inequality is a global issue caused by unequal access to resources and wealth. Islamic economics offers a solution through a just and ethical approach to wealth distribution. This study explores Islamic instruments such as zakat, infāq, ṣadaqah, and waqf as tools to reduce inequality and promote social welfare. Using a qualitative library research method, the study finds that these mechanisms help redistribute wealth, strengthen social solidarity, and support inclusive development. In the digital era, innovations like Islamic fintech, crowdfunding, and digital waqf expand access to financial services while staying true to Islamic values. However, challenges such as low financial literacy and regulatory barriers persist. To optimize the role of Islamic economics, it is essential to strengthen institutions, improve regulations, and promote public awareness. These efforts can enhance its contribution to building a fair and sustainable economy.